2012
DOI: 10.1097/01.aoa.0000414096.18773.f5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Massive Blood Loss in Women With Placenta Accreta

Abstract: O bstetric hemorrhage is the cause of 10% of maternal deaths in the United States, and occurs in more than 600,000 women a year. One of the most common causes of obstetric hemorrhage is abnormal placentation. Past cesarean deliveries directly increase the risk of placenta accreta. Peripartum hysterectomy is often the treatment for placenta accreta but is associated with morbidity and requires large quantities of blood products in a small time span. The goal of this study was to establish predictors of massive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 0 publications
2
48
0
1
Order By: Relevance
“…In this study, parity and the number of previous cesarean sections were significantly high among women who had difficult placental delivery, considerable intraoperative blood loss, who required emergency hysterectomy to control bleeding. Wright et al (29) found that 41.7% of women with a known placenta accreta had a blood loss of ≥5000 mL, and, although Wright et al (29) concluded that there was no significant relation between parity, number of previous cesarean deliveries, degree of placental invasion, and massive blood loss, Tikkanen et al (30) found that the risk factors of placenta accreta included parity, cesarean section, and placenta previa. In addition, Guleria et al (31) concluded that the risk factors of abnormal invasive placentation (AIP) were placenta previa and a past history of cesarean delivery, and Thia et al (32) concluded that the depth of invasion in MAP is increased with multiple previous surgeries or excessive curettage or infection causing defective decidua basalis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, parity and the number of previous cesarean sections were significantly high among women who had difficult placental delivery, considerable intraoperative blood loss, who required emergency hysterectomy to control bleeding. Wright et al (29) found that 41.7% of women with a known placenta accreta had a blood loss of ≥5000 mL, and, although Wright et al (29) concluded that there was no significant relation between parity, number of previous cesarean deliveries, degree of placental invasion, and massive blood loss, Tikkanen et al (30) found that the risk factors of placenta accreta included parity, cesarean section, and placenta previa. In addition, Guleria et al (31) concluded that the risk factors of abnormal invasive placentation (AIP) were placenta previa and a past history of cesarean delivery, and Thia et al (32) concluded that the depth of invasion in MAP is increased with multiple previous surgeries or excessive curettage or infection causing defective decidua basalis.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] During caesarean section the volume of blood loss in placenta accreta is so great that it often exceeds several times the total blood volume of the patient. [5][6][7] On the background of previously submitted data about a huge amount of blood loss in placenta accreta appear unique results presented by the English authors, which report about the development and implementation of their own new interdisciplinary methods, called "Triple-P". When using this method, the average intraoperative blood loss was 1440ml (ranges from 800ml to 2,900ml).…”
Section: Introductionmentioning
confidence: 99%
“…Dentro de las principales indicaciones para realizar la HO se encuentra la hemorragia obstétrica por atonía uterina, las laceraciones del útero y los procesos infecciosos, pero sin duda es la hemorragia por atonía la principal indicación (3). El procedimiento tiene alta morbilidad cuando la hemorragia es secundaria a adherencia anómala de la placenta, a placenta previa o desprendimiento prematuro de placenta normo inserta, principalmente por choque hipovolémico o séptico, coagulación intravascular diseminada y lesiones de vías urinarias.…”
Section: Introductionunclassified